2008
DOI: 10.1021/jp0775193
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Adsorption on the Si(100) Surface:  The Case of Glycine

Abstract: Using first principles total energy methods, we have investigated the adsorption of glycinethe simplest amino acidon the Si(100)- c(4 × 2)surface, with a focus on the associated energetics, charge transfer, electronic properties, and structural characteristics. We find that glycine adsorbs primarily on the “down” atoms of a Si dimer, with adsorption of the amino group being slightly favored over the absorption of the carboxylic acid group. Glycine on Si(100) may also involve the removal of a H atom from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The energetics of the adsorption process of glycine on the Si(100) surface has been studied from a theoretical point of view in several previous works. [6][7][8]59 In particular, several conceivable configurations of adsorbed glycine have been analysed through periodic calculations, 7 taking into account different binding schemes. Such studies showed that the most favourable mechanisms involve the dissociation of one of the hydrogen atoms (from either -NH 2 or -COOH groups), which in turn binds the silicon surface.…”
Section: Energetics Of the Adsorption Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The energetics of the adsorption process of glycine on the Si(100) surface has been studied from a theoretical point of view in several previous works. [6][7][8]59 In particular, several conceivable configurations of adsorbed glycine have been analysed through periodic calculations, 7 taking into account different binding schemes. Such studies showed that the most favourable mechanisms involve the dissociation of one of the hydrogen atoms (from either -NH 2 or -COOH groups), which in turn binds the silicon surface.…”
Section: Energetics Of the Adsorption Processmentioning
confidence: 99%
“…[1][2][3] In this respect, even the simplest natural amino acid, glycine (NH 2 CH 2 COOH), represents a rather complicated molecular model, in view of its bi-functional characteristics related to the contemporary presence of a basic (-NH 2 ) and an acidic (-COOH) group, which could lead to several different binding schemes. [4][5][6][7][8] Moreover, interaction between complementary functional groups of neighboring ad-molecules through hydrogen bonding can be used to form ordered microarrays. Additionally, with one of the functional groups bonded to the surface and the other one free to interact with incoming molecules, glycine is also a simple yet realistic test-case of linker molecules able to form multilayer structures by hydrogen bonding for bio-device and molecular electronics applications.…”
Section: Introductionmentioning
confidence: 99%
“…When adsorption of amino acids at polar or charged surfaces is experimentally observed, it tends to involve chemical reactions such as hydroxyl transfers which are often not reversible , and in which desorption can involve fracturing of the molecule. , The other major mode of adsorption on these surfaces is driven by electrostatic interactions between amino acids and surface sites with high charge density. ,, The former mode of adsorption is unacceptable for applications such as chromatography which depend on reversible and rapid adsorption and desorption. The latter mode is useful to separate charged amino acids, but not applicable to others.…”
Section: Introductionmentioning
confidence: 99%
“…However, our research utilized the use of low buckled silicene structure. The electronic properties of this structure differs slightly from those of the high buckled silicene structure (Luo et al, 2008). We inferred that the charge transfer between the Si dn and Si up atoms were not complete, leaving neither atom completely empty or completely full.…”
Section: Carbon Dioxide On Pure Silicenementioning
confidence: 74%